Multilevel X-ray imaging approach to assess the sequential evolution of multi-organ damage in multiple sclerosis - Francesca Palermo; Nicola Pieroni; Alessia Sanna; Benedetta Parodi; Consuelo Venturi; Ginevra Begani Provinciali; Lorenzo Massimi; Laura Maugeri; Gian Paolo Marra; Elena Longo; Lorenzo D’Amico; Giulia Saccomano; et al. (Communications Physics, 2022)
X-ray phase-contrast tomography offers a highly sensitive 3D imaging approach to investigate different disease-relevant networks at levels ranging from single cell through to intact organ. The authors present a concomitant study of the evolution of tissue damage and inflammation in different organs affected by the disease in the murine model for multiple sclerosis.